Effects of single-dose hexavalent chromium on growth performance and biochemical parameters of swiss albino female mice: Hexavalent chromium Toxicity in Swiss Albino Female Mice - Fahim, FJ; Rahman, MM; Akhand, MRN; Islam, S (Journal of the Sylhet Agricultural University, 2025)
Hexavalent chromium, hazardous metal, have a range of harmful consequences, including developmental toxicity, and they infiltrate the human and animal food chains due to untreated effluents emitted. Since hexavalent chromium affects both animals and humans, the aims of the current experiment were to assess the impacts of a single intraperitoneal dosage on body weight and biochemical markers (ALT, AST, and TP) as well as on hormone (progesterone) levels in female Swiss albino mice. A total 24 healthy adult mice were divided into three groups consisting of six mice per group, including control T0, and treatment groups T1 and T2 with a single dose of Cr (VI) at a dosage rate of 1 and 2 mg/kg body weight was done using an intraperitoneal administration respectively. The significance of the difference between groups was tested using a single-factor ANOVA. On the 14th day following injection of hexavalent chromium, visceral organs such as the lung, heart, liver, spleen, kidney, and blood were taken. Exposure to Cr (VI) produced a substantial decline (p<0.05) in weight gain coupled with considerably enhanced weight gain of the liver, kidney, and spleen (p<0.05). The activity of the enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST) was statistically highly enhanced (p>0.05), along with the exponentially significant elevated level of total protein (p<0.01). No significant variation was noticed in the progesterone hormone level (p > 0.05) among the treated groups and the control group. The outcomes of the current investigation indicated that experimental female albino mice exhibited harmful effects following injection of chromium VI. J. Sylhet Agril. Univ. 11(2): 11-18, 2024